Differentiating Ammonia from Other Reducing Gases via Response Reversal Phenomena by Varied ZnO/CuxO Nanorod Arrays. Issue 11 (1st January 2018) - Wang, Ruey-Chi; Hou, Yuan-Ru; Liu, Jia-Yu; Chen, Yi-Wen
Abstract : Semiconductor gas sensors have attracted much attention, but poor specificity limits their practical applications. In the current work, a universal design with varied n-p core-shell structures was proposed to distinguish NH3 gas from other reducing gases by a p-n competition mechanism. Acting as a model system, devices made of n-ZnO/p-Cux O core-shell nanorod (NR) arrays with variable shell thicknesses prepared by a two-step route demonstrate this unique gas specificity behavior. The transmission electron microscopy results show the outer Cux O shells on the surface of NRs are comprised of major Cu2 O and minor CuO crystals. When the shell thickness is greater than a critical value, the NR devices exhibit a p-type response to all the testing reducing gases. When the shell thickness is less than the critical value, only NH3 among the testing reducing gases results in an unusual n-type response, which demonstrates extraordinary discernment to ammonia gas by only observing the trend in the increase or decrease of resistance. A thickness-dependent band structures upon gas sensing is proposed to explain the improved gas specificity.